State Creation and Socioeconomic Development in Nigeria: A Political Economy Analysis - Charles B Berebon (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2024)
This study presents a longitudinal historical analysis of the state creation exercises in Nigeria and their potential to stimulate socioeconomic development in the regions that benefit from such restructuring. Both the government and proponents of state creation in Nigeria view the process as a critical driver for advancing development in previously underdeveloped areas. The expectation is that state creation can promote balanced development, distributing socioeconomic amenities and opportunities more evenly across the new states, particularly benefiting the capital cities, urban towns, and eventually rural areas. However, evidence suggests that past state creation efforts have inadvertently fueled rural-urban migration, as development efforts have primarily focused on urban centers, leaving rural areas neglected and disadvantaged. This urban-centric development pattern has undermined the intended goal of fostering widespread socioeconomic growth. The prevailing belief that state creation serves as a catalyst for socioeconomic development has likely intensified the persistent and vigorous demands for new states across different regions of the country. This study critically examines these dynamics, exploring the implications of state creation on regional development and evaluating whether the anticipated benefits have been realized or if the process has merely perpetuated existing inequalities.